Konseling Individu untuk Meningkatkan Konsep Diri Siswa Penyandang Tunarungu - Rizal Adicita (Faculty of Psychology, Universitas Semarang, 2017)
This study aims to produce and determine the effectiveness of individual rehabilitation counseling service models to develop the self-concept of deaf students. The self concept of deafblower students is proven to be low after a pretest. A low self-concept will lead to deaf students experiencing stress. The hypothesis proposed by the researcher is that there is an effectiveness of individual rehabilitation counseling models to develop self-concept of deaf students. This research method uses research and development approaches. Individual rehabilitation counseling to develop the self-concept of deaf students was given to 8 students as the research subjects selected by purposive sampling in Semarang Regency SLB. The results showed that the individual rehabilitation counseling model effectively developed the self-concept of deaf students. This is indicated by changes in the level of self-concept before being given treatment (pre-test) and after being given treatment (post-test) there was an increase in the initial evaluation score of 862 points to 966 points or an increase of 134 points, so the hypothesis in this study was accepted.